AB1070 MICROVASCULAR NAILFOLD ALTERATIONS BY VIDEOCAPILLAROSCOPY IN PATIENTS WITH RHEUMATOLOGICAL SYMPTOMS WITH JUVENILE INFLAMMATORY BOWEL DISEASE. (June 2019) - Villarreal-Trevino, Ana; García-Rodriguez, Fernando; Rubio-Perez, Nadina; Fernández-Ortiz, Sergio
Abstract : Background: Juvenile Inflammatory Bowel Disease (jIBD) is a chronic relapsing inflammatory condition of the gastrointestinal system that includes Crohn's disease (CD) and Ulcerative Colitis (UC) and develops during childhood or adolescence in up to 25% of patients and affects the patients and parent ś quality of life. Endothelial dysfunction is considered one of the etiological factors of jIBD. Nailfold videocapillaroscopy is one of the best and safest diagnostic non-invasive imaging techniques to analyze microvascular abnormalities. Previous studies describe the involvement of the microvasculature in the pathogenesis of this diseases, suggested that chronic mesenteric vasculitis is a pathogenetic mechanism in CD. Nailfold abnormalities founded are similar to those observed in some systemic vasculitidies. Subpapillary venous plexus dropout and low vessel density were previously reported. Objectives: In this abstract we describe nailfold videocapillaroscopy findings in patients with jIBD and their correlation with disease activity. Methods: This is a prospective and analytical study thad recruited pediatric patients between 2 and 18 years with jIBD. A single cross-sectional 8-finger nailfold videocapillaroscopy was performed using a 200x optical probe videocapillaroscope. The images were collected, encoded and stored using the Optipix® software. Qualitative, quantitative and semi-quantitative assessment for architecture were scored following the international definitions for the capillary abnormalities Blood chemistry, C-reactive Protein, erythrocyte sedimentation rate, antineutrophil cytoplasmic antibody, and calprotectin were performed. Sociodemographic data, clinical eva- luation, confirmation of IBD criteria, disease history, and activity evaluation were collected from patients clinical records. Statistics were performed using Spearman test to evaluate the correlation coefficient between the variables under study. Results: 10 patients with jIBD were included 60% male, 50% Ulcerative Colitis and 50% Crohn ś Disease. 20% had severe disease according the Pediatric Ulcerative Colitis Activity index, Pediatric Crohon ś Disease activity index showed mild activity in just one patient. Rheumatological manifestations were found in 40%, 4 had arthritis, systemic vasculitidies in 2 and 10% hematological manifestations. Abnormal endoscopy in 60% showing pancolitis. Normal microvasculature pattern were only found in 3 patients (25%), microangiopathy was found in 75%, edema of the nailfold bed was present in n=6 patients, a low capillary density was found in 100% of the patients with disease activity. A statistical negative correlation between the number of capillarities per millimeter and disease activity was found (coefficient -0.936, p=0.001). Conclusion: Previous data showed that low capillary density was find in patients with jIBD, the data in this pilot study are consistent with those findings. The assessment of the microvasculature through the use of videcapillaroscopy could be useful in this diseases. References: 1. Deban et al. Multiple Pathogenic Roles of Microvasculature in Inflammatory Bowel Disease: A Jack of All Trades. AJP June 2008, Vol. 172, No. 6 1457-1466 Disclosure of Interests: None declared